-(-15v-4)=2(v-5)+11v

Simple and best practice solution for -(-15v-4)=2(v-5)+11v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(-15v-4)=2(v-5)+11v equation:



-(-15v-4)=2(v-5)+11v
We move all terms to the left:
-(-15v-4)-(2(v-5)+11v)=0
We get rid of parentheses
15v-(2(v-5)+11v)+4=0
We calculate terms in parentheses: -(2(v-5)+11v), so:
2(v-5)+11v
We add all the numbers together, and all the variables
11v+2(v-5)
We multiply parentheses
11v+2v-10
We add all the numbers together, and all the variables
13v-10
Back to the equation:
-(13v-10)
We get rid of parentheses
15v-13v+10+4=0
We add all the numbers together, and all the variables
2v+14=0
We move all terms containing v to the left, all other terms to the right
2v=-14
v=-14/2
v=-7

See similar equations:

| 2p-p-1=6 | | X-35+y=65 | | 11-2r+6r=r+3+2 | | -11+-6r=8r+5 | | 3/4n=-1+3/4n-18 | | 5x/3-x=x/15-6/15 | | 40x+10-25x-5=-12x+15 | | 2/5x+1+3/5x=0 | | 58=7x-5= | | -(-15v-4)=2(v-5)=11v | | -21/2(1/2x-12)=6(2x7) | | x=25/10= | | 5-4x+3x=5-5x | | m·10−m·13=138 | | 4x^2=13.7 | | y=3×-38 | | 1(6x+5)=43 | | m*10−m*13=138 | | 3d+10+2d=-3d-30 | | 220-2x=180-x | | X+12+3x-2=90 | | 7=4x-70 | | 9x+7=-3x+8 | | (10x+38)+(18x-2)=90 | | 5x-3+1x+50-2x=180 | | 2=2x+44 | | 6x4=24/8-3 | | (10x+38)+(18x-2)=180 | | -8(-7v+8)-6v=28+4v | | 4x+8-3x=8x=6-7x | | 8p=6(3p+6)=6 | | 11x+66=11 |

Equations solver categories